The response of macro variables of emerging and developed oil importers to oil price movements - Farhad Taghizadeh-Hesary; Naoyuki Yoshino; Majid Mohammadi Hossein Abadi; Rosa Farboudmanesh (Asian Development Bank Institute (ADBI), 2015)
This paper assesses the impact of crude oil price movements on two macro variables - the gross domestic product (GDP) growth rate and consumer price index inflation rate - in the developed economies of the United States and Japan, and an emerging economy, the People's Republic of China (PRC). These countries were chosen for this research because they are the world's three largest oil consumers. The main objective of this study is to see whether these economies are still reactive to oil price movements. The results obtained suggest that the impact of oil price fluctuations on the GDP growth of the developed oil importers is much lower than on the GDP growth of the emerging economy. The main reasons for this lie in fuel substitution (higher use of nuclear energy, gas, and renewables), a declining population (for Japan), the shale gas revolution (for the United States), and strategic oil stocks and government-mandated energy efficiency targets in developed economies. All of these factors make developed economies more resistant to oil shocks. On the other hand, the impact of oil price movements on the PRC's inflation rate was found to be milder than in the two developed countries that were examined. The main cause for this is that the PRC experiences a larger forward shift in its aggregate supply due to higher growth, which allows it to avoid a massive increase in price levels following oil price shocks.
Keywords: Q43; E31; O57; 330; oil price movements; oil importers; oil consumption; fuel substitution; price shocks